The disproportionately high value of small patches for biodiversity conservation - Riva, Federico; Fahrig, Lenore (Conservation letters, 2022)
Small habitat patches have been historically neglected in conservation, primarily because extinction risk is higher in small patches. Nevertheless, sets of small patches usually harbor more species than one or a few larger patches of equal total area. Resolving this inconsistency is key to policy and practice in biodiversity conservation. Our analysis of 32 datasets (603 patches and 2290 taxa) provides two novel lines of evidence confirming that small patches have disproportionately high value for biodiversity. First, sets of small patches harbor more species than large patches even when considering only species of conservation concern. Second, sets of small patches harbor more species than large patches even when the small patches are very small compared to the large patches. Therefore, higher extinction risk in small than large patches does not decrease the cumulative value of small patches for biodiversity. We contend that acknowledging the conservation value of small patches, even very small patches, will be a necessary step for stemming biodiversity loss in the Anthropocene.